Pengaruh Citra Kuliner Tradisional terhadap Keputusan Pembelian di Gado-Gado Boplo Cabang Cikini - Kezya Laurens Putri Antonia; Dewanta Facrureza (Lembaga Pengembangan Kinerja Dosen, 2024)
This research examines the phenomenon of Gado-Gado Boplo as a legendary eating place recognized by Kompas, Flokq, and Nibble articles. The research uses quantitative methods using questionnaires via Google Form and secondary data from the internet, journals and interviews. The sample used was 100 people who had eaten at Gado-Gado Boplo using a Likert scale. All questions were declared valid, with a calculated R value > R table, after which the data was evaluated using Cronbach's alpha for reliability and Pearson Correlation for validity. Apart from that, the Cronbach alpha data value > 0.6 shows its reliability. The data was then subjected to multiple regression analysis, classical assumption testing, and hypothesis testing (T and F tests). The Excellence variable (X3) has a partially significant influence on the Purchasing Decision variable (Y), but the Strength (X1) and Uniqueness variables (X2) do not have a partial influence on the Purchasing Decision variable (Y), according to the T test. Furthermore, jji F shows that variables X1, X2, and X3 all influence Y significantly at the same time. In conclusion, superiority has a favorable and large influence on purchasing choices, but strength and uniqueness only have a small influence. These three X factors all have a significant influence on purchasing choices (Y) at the same time.